The Study of Redox Electrode Processes of Sulfur-Containing Compounds by Voltammetry; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Dorozhko E. V. Elena Vladimirovna; Korotkova E. I. Elena Ivanovna; Kataev S. G.; Voronova O. A. Olesya Aleksandrovna; Plotnikov E. V. Evgeny Vladimirovich; Derina K. V. Kseniya Vladimirovna (2015, 2015)
Title screen